Advancing food safety with biogenic silver nanoparticles: Addressing antimicrobial resistance, sustainability, and commercial viability - Himanshu Jangid; Harish Chandra Joshi; Joydeep Dutta; Akil Ahmad; Mohammed B. Alshammari; Kaizar Hossain; Gaurav Pant; Gaurav Kumar (Food Chemistry: X)
The escalating threat of antimicrobial resistance (AMR), particularly among foodborne pathogens such as Escherichia coli, Salmonella enterica, and Listeria monocytogenes, necessitates innovative solutions beyond conventional antimicrobials. Silver nanoparticles (AgNPs) have garnered significant attention for their broad-spectrum antimicrobial efficacy, ability to target multidrug-resistant strains, and versatile applications across the food sector. This review critically examines AgNPs' integration into food safety strategies, including their roles in antimicrobial food packaging, agricultural productivity enhancement, and livestock disease mitigation. Key advancements in eco-friendly synthesis methods, leveraging algae, agricultural byproducts, and microbial systems, are highlighted as pathways to address scalability, sustainability, and cost constraints. However, the potential risks of silver bioaccumulation, environmental toxicity, and regulatory challenges present significant barriers to their widespread implementation. By reviewing cutting-edge research, this review provides a comprehensive analysis of AgNP efficacy, safety, and commercial viability, proposing a roadmap for overcoming current limitations. It calls for collaborative, interdisciplinary efforts to bridge technological, ecological, and regulatory gaps, positioning AgNPs as a transformative solution for combating AMR and ensuring global food security.